Genetic Predisposition to Severe COVID-19 Might Increase the Risk of Stroke: A Two-Sample Mendelian Randomization Study - Zhang, Jinji; Wu, Fayong; Chen, Shenge; Zhu, Ying; Luo, Xian; Qiu, Xiaolin (Frontiers in Genetics, 2022)
Aims: he causal relationship between COVID-19 infection and stroke has not yet to be fully established. This study aimed to explore this causality by two-sample Mendelian randomization (MR). Materials and methods: Genetic variants associated with COVID-19 infection and stroke were both obtained from genome wide association study (GWAS) summary data. The single nucleotide polymorphisms (SNPs) were selected as instrumental variables. The standard inverse variance weighted (IVW) was primarily used to assess this causality. Finally, sensitivity analysis was performed to evaluate the reliability and stability. Results: The results showed that hospitalized due to COVID-19 had a positive effect on stroke [OR=1.05; 95% CI= (1.01, 1.10); P=2.34×10-5] and ischemic stroke [OR=1.06; 95%CI= (1.02, 1.11); P=2.28×10-6] analyzed by IVW. Moreover, the results revealed that severe respiratory symptoms due to COVID-19 had a positive effect on the stroke [OR=1.04; 95%CI= (1.00, 1.06); P=0.04], besides, the causal effect of severe respiratory symptoms due to COVID-19 on ischemic stroke estimated by IVW suggested a positive effect [OR=1.06; 95%CI= (1.02, 1.09); P=0.0068], too. Conclusions: In summary, this study showed that severe COVID-19 might increase the risk of stroke, thus much more attentions should be paid to patients with severe COVID-19.